Canvassing Greek Academic Librarians’ Opinion of Their Organizations’ Position on the Library Evolution Continuum - Sant-Geronikolou, Stavroula; Martínez-Ávila, Daniel (Journal of Integrated Information Management, 2019)
Purpose - The study analyzes academic librarian convenience sample’s responses to an online survey seeking to identify the current innovation and transformation facts and figures of the Greek academic library in the overarching aim to contribute to the higher education community knowledge base on current trends and challenges along the academic librarianship evolution continuum. Design/methodology/approach – The research involved the distribution of a questionnaire that sought to investigate library staff perspectives and considerations about service provision, innovation adoption, and organizational development-related aspects. It was further complemented with additional contextual information resulting from the inspection of official library webpages. Findings - The survey results representing 25 Greek higher education Institutions through responses received by administrative and executive staff in 22 central and nine academic branch libraries indicate academic library services with the highest and lowest statistical presence. Partnerships development is acknowledged as a top library transformation motivator while budgetary, infrastructural, and staffing issues are listed at the top of the library transformation inhibitors. There were also indications of insufficient strategic planning. Findings also suggest the need to enhance organizational development processes for sustaining and increasing innovation by transforming the library into a double loop learning organization.